ANALISIS YURIDIS TERHADAP TINDAK PIDANA PENCEMARAN NAMA BAIK DAN BERITA BOHONG - Kesuma, Derry Angling; Triputra, Yuli Asmara (Solusi, 2024)
The problem that the author raises is regarding the reason why the Constitutional Court decided to grant part of the judicial review lawsuit filed by Haris Azhar and Fatia Maulidiyanti, and to remove Article 14 and Article 15 of Law Number 1 of 1946 concerning Criminal Law Regulations regarding the spread of fake news or hoaxes. by using normative legal research methodology, The Constitutional Court has decided and granted part of the judicial review lawsuit filed by Haris Azhar and Fatia Maulidiyanti, which then removed Article 14 and Article 15 and Article 310 of Law Number 1 of 1946 concerning Criminal Law Regulations regarding the spread of fake news or hoaxes. "In the main petition, granting the petitioners' petition in part. Declaring that Article 14 and Article 15 of Law Number 1 of 1946 concerning Criminal Law Regulations (State Gazette of the Republic of Indonesia II Number 9) are contrary to the 1945 Constitution of the Republic of Indonesia and do not have binding legal force," said Chief Justice Suhartoyo in Jakarta. The state may not reduce freedom of opinion with absolute provisions or conditions that what is conveyed is something that is true or not a lie. The Constitutional Court also stated that the elements of "fake news or notification" and "uncertain news, or excessive news" in Article 14 and Article 15 of Law No. 1 of 1946 are norms that contain restrictions on expressing opinions freely in the public sphere. Therefore, the Constitutional Court is of the opinion that the norms in Articles 14 and 15 of Law No. 1 of 1946 can trigger the occurrence of rubber articles that can create legal uncertainty. Regarding the application of Article 310 paragraph (1) of the Criminal Code, the Constitutional Court decided that the article was unconstitutional. The Constitutional Court changed the wording of the article to "anyone who intentionally attacks the honor or good name of a person by accusing them of something verbally, the intention of which is clearly so that it is known to the public, is threatened with defamation with a maximum prison sentence of nine months or a maximum fine of four thousand five hundred rupiah".